Comparative analysis of the taxonomic structure of microalgae in bays and estuaries of the Black Sea–Azov region - Bren, O.G.; Bren, O.A.; Podorozhny, S.M. (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2026)
Bays and estuaries of the Black Sea–Azov region are characterized by pronounced hydrological variability, which creates a wide range of environmental conditions and influences the taxonomic structure of microalgae. Despite the substantial number of studies, available data are mostly reported for separate water bodies, which complicates their comparison. In this study, published data on the taxonomic structure of microalgae were compiled and comparatively analysed at the level of phyla and classes using multivariate statistical approaches, including ordination (NMDS) based on the Bray–Curtis index, permutational multivariate analysis of variance (PERMANOVA), and analysis of the contribution of individual taxa to differences between water body types (SIMPER). In bays, Bacillariophyta and Dinoflagellata had generally comparable species proportions, whereas in estuaries Bacillariophyta comprised substantially more species, while Dinoflagellata were represented by few species or were absent in several water bodies. These differences indicate patterns in the taxonomic structure of microalgae between bays and estuaries of the Black Sea–Azov region and could be considered in ecological monitoring.